Subjective and Cardiovascular Responses to an Acute Laboratory Gambling Task in Men and Women - Miller, Louise; Söderpalm Gordh, Anna (Frontiers in Psychiatry, 2022)
Men have previously been overrepresented in gambling for money but in recent years there has been an increase in recognition that women who gamble are ‘catching up’ with their male counterparts. There have been few experimental studies investigating the subjective effects of gambling, and even less have explored the gender differences. As gender differences previously have been reported in the subjective effects of several drugs of abuse such as opioids, amphetamines and alcohol, we sought to investigate if the subjective effects of gambling also differed by gender. The present article analyzes if gender modulates the subjective and physiological effects of an acute laboratory gambling task in healthy men and women. Eighty-two men and women (n=35 men, n=47 women) were tested with an online slot machine gambling session and self-report questionnaires of mood and blood pressure were taken before and after gambling. Both men and women showed stimulatory effects of gambling i.e. feelings of high and euphoria but no differences were found between genders. Findings suggest that both men and women equally experience a pattern of stimulatory effects of gambling from the gambling situation. Gambling therefore seems to have the same abuse potential in both men and women. Although the gap between men and women is narrowing, immediate subjective and physiologic responses do not explain gender differences in the epidemiology of pathological gambling. The contexts and factors that foster or hinder the evolution of gambling addiction in males and females should be further explored. This conclusion is interesting in light of that men are over three times more at risk to experience gambling related problems than women and this risk may depend on other factors involved in the development of addiction.